PROSES PEMBUKTIAN DALAM PENYIDIKAN TINDAK PIDANA KEKERASAN FISIK DALAM RUMAH TANGGA - Surya Darma Siregar, Darlisma (Menara Ilmu, 2018)
To support the creation of a sense of security for every individual within the scope of thehousehold, Law No. 23 of 2004 on the Elimination of Domestic Violence (KDRT) explicitlyexplains that everyone is prohibited from domestic violence against persons within the scope oftheir household by: a. Physical Abuse b. Fsychic violence c. sexual assault and d. abandonment ofhousehold. In writing this essay, the authors categorize the two problems is how the process ofproof in the investigation of criminal acts of physical violence in the household and what the legalbasis added the witness other than the victim's witness in the investigation of criminal acts ofphysical violence in the household. The research method used is empirical juridical method, whiledata collection is obtained through interviews and written data sources from library or libraryresearch.From the research result, it can be seen that the proof process in the investigation of thecrime of physical violence in the household in Pasaman Police refers to Article 55 of Law Number23 Year 2004, which to determine a person as a suspect, the investigator can find evidence ofvictim testimony which is supplemented with other evidence of visum et repertum examinationresults. However, the investigator is also not wrong to add other witnesses other than victimwitnesses because there are no rules that prohibit about it.Keywords: Evidence, investigation, crime, physical violence in the household,